Statins as Either Immunomodulators or Anti-Cancer Drugs: Functional Activities on Tumor Stromal Cells and Natural Killer Cells - Poggi, Alessandro; Musso, Alessandra; Boero, Silvia; Canevali, Paolo; Zocchi, Maria R. (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2010)
It has been extensively shown that statins, inhibitors of 3-hydroxyl-3-methylglutaryl coenzyme A (HMG-CoA) reductase can effectively be used in the treatment of hypercholesterolemia. Indeed, coronary morbidity and mortality related to atherosclerotic plaque dependent cardiovascular diseases have been greatly reduced by their employment. Recently, it has been shown that statins can affect cell growth and survival of solid tumours and leukaemic cells. Indeed, it has been proposed their employment in multiple myeloma treatment in association with thalidomide or its derivatives. On the other hand, statins have strong anti-inflammatory and immunomodulatory effects and thus they may have a role in the regulation of anti-tumour immunity. Indeed, there are several evidences that inflammation may promote oncogenesis and, on the other hand, inflammation may participate in cancer rejection. Herein, we analyze the effects that statins can exert on cancer cells, stromal cells in tumor microenvironment and anti-tumor cytolytic activity of human natural killer cells.
Keywords: natural killer cells